PENGARUH LOKASI TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN TYPE 36 PADA PT. WAHANA TATA GRIYA PEKANBARU - ', Herman (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract : The research was conducted on the PT. Wahana Tata Griya project, namely residential Griya Savana Sukajadi 2 on Sukajadi Street Kampar district. This research study tostudy the Effect of Location on Decisions the purchase of Perumahan type 36 in PT. WahanaTata Griya Pekanbaru City. In analysing data obtained from research objects usingquantitative analysis and 45 respondents., using the SPSS program using simple linearregressons analysis method. From the regression results in this study, the following regressionequation can be know : Y = 11,358 + 0,657X, estimated value of 11,358, this value refers towhen the location variable ( variable X) is zero, then decision the purchase (variable Y) is11,358 while the value of b is 0,657, meaning that the compilation increase the value of the location variable ( variable X) by 1 (one) unit, then decision the purchase on (variable Y) will increase by 0,657 units. T value of 8,664. While the critical value according to the table with significance level 5% using the formula t table (α / 2; n-k) k=2 and n= 45-2 = 43 is 2,01669, because t count > t table then Ho is rejected. The importance of the influence of location variables on decisions the purchase variable. With the meaning of the word Hypothesis (Ha)accepted. Positive t value indicates variables require a direct relationship with decision the purchase at PT. Wahana Tata Griya Pekanbaru. The coefficient of determination (R Square) of63,6 or 63,6%. So it can be concluded that location variables by 63,6%. While the remaining36,4% (100%-63,6%).